Plant in vitro Culture Technologies; A Promise Into Factories of Secondary Metabolites Against COVID-19 - Khan, Tariq; Khan, Mubarak Ali; Karam, Kashmala; Ullah, Nazif; Mashwani, Zia-ur-Rehman; Nadhman, Akhtar (Frontiers in Plant Science, 2021)
The current pandemic has caused chaos throughout the world. While there are few vaccines available now, there is the need for better treatment alternatives in line with preventive measures against COVID-19. Along with synthetic chemical compounds, phytochemicals cannot be overlooked as candidates for drugs against severe respiratory coronavirus 2 (SARS-CoV-2). The important role of secondary metabolites or phytochemical compounds against coronaviruses has been confirmed by studies that reported the anti-coronavirus role of glycyrrhizin from the roots of Glycyrrhiza glabra. The study demonstrated that glycyrrhizin is a very promising phytochemical against SARS-CoV, which caused an outbreak in 2002–2003. Similarly, many phytochemical compounds (apigenin, betulonic acid, reserpine, emodin, etc.) were isolated from different plants such as Isatis indigotica, Lindera aggregate, and Artemisia annua and were employed against SARS-CoV. However, owing to the geographical and seasonal variation, the quality of standard medicinal compounds isolated from plants varies. Furthermore, many of the important medicinal plants are either threatened or on the verge of endangerment because of overharvesting for medicinal purposes. Therefore, plant biotechnology provides a better alternative in the form of in vitro culture technology, including plant cell cultures, adventitious roots cultures, and organ and tissue cultures. In vitro cultures can serve as factories of secondary metabolites/phytochemicals that can be produced in bulk and of uniform quality in the fight against COVID-19, once tested. Similarly, environmental and molecular manipulation of these in vitro cultures could provide engineered drug candidates for testing against COVID-19. The in vitro culture-based phytochemicals have an additional benefit of consistency in terms of yield as well as quality. Nonetheless, as the traditional plant-based compounds might prove toxic in some cases, engineered production of promising phytochemicals can bypass this barrier. Our article focuses on reviewing the potential of the different in vitro plant cultures to produce medicinally important secondary metabolites that could ultimately be helpful in the fight against COVID-19.